Docentes mães: covid-19, perspectivas de gênero e os desafios das múltiplas jornadas de trabalho - Pletiskaitz, Katiúcia (2024)
This study is part of the LP2 - Public Educational Policies, Educational Practices and their Interfaces of the Graduate Program in Education, at the Federal University of Santa Maria. The research problem is: “what are the impacts of the accumulation of roles in the private environment for women mothers, teachers of early childhood education, during the COVID-19 pandemic?”. As the general objective of this study, we sought to understand how teachers of municipal Early Childhood Education reconciled domestic work, maternity and professional performance during the COVID-19 pandemic in Santa Maria/RS. The specific objectives achieved were: to identify the intersection related to gender, race and class; the sociocultural and professional impacts on the life of the research participants; to highlight the potential and weaknesses of remote teaching work in line with care and other activities developed by women; and reflect on the strategies for adaptations of daily life and impacts in the post-pandemic period, as regards personal life, familiar and professional of the research participants. The methodology uses a qualitative approach; as data production techniques, semi-structured interviews were used, whose results were analyzed under the perspective of discursive textual analysis (Moraes; Galiazzi, 2006, 2016) and had constructionist reflexivity (Colombo, 2016) through the process of research construction, from its origin to the critical description of the results. The study revealed that the mother teachers faced challenges in balancing remote work with domestic responsibilities, but also highlighted the creative strategies they developed to deal with the overload, highlighting both the difficulties and opportunities of this context. The survey was conducted in the city of Santa Maria/RS, in the years 2022/2023, delimiting five municipal schools of Early Childhood and Elementary Education that attend classes of Early Childhood Education and have teachers-mothers working in Early Childhood Education, with children from zero to six years old and who have acted remotely during the COVID-19 pandemic period (2020 to 2022). The study points to the need for public policies that offer adequate support to teachers, promoting the balance between personal and professional life. For the theoretical foundation, authors such as Akotirene (2020), Antunes (2009, 2020, 2021), Badinter (1985, 2010), Moraes and Galiazzi (2006, 2016), Galvão and Saviani (2021), Iaconelli (2021, 2023), Taperman, Garrafa and Iaconelli (2020), Kitzinger (1978), Martins Filho (2021), Saffioti (1987, 2000, 2004) and Santos (2020) were used, among others, that contributed to the discussions presented.